A peptide-DNA hybrid bio-nanomicelle and its application for detection of caspase-3 activity - Zhang, Fan; Mao, Changqing; Cao, Siyu; Zhang, Runchi; Guo, Yi; Chen, Guifang; Feng, Chang (Frontiers in Chemistry, 2022)
Bio-nanomicelles based on biomaterials such as nucleic acids, peptides, glycans, and lipids have developed rapidly in the field of bioanalysis. Although DNA and peptides have unique advantages, unfortunately, there are few bio-nanomicelles integrating DNA with peptides. Here, we designed a peptide-DNA hybrid bio-nanomicelle for the activity detection of caspase-3. The detection mechanism is based on caspase-3 specific recognition and cleavage of peptide substrates, which owns high sensitivity and selectivity. Under optimal conditions, the detection of caspase-3 activity can be achieved using our designed bio-nanomicelles and the detection limit is 0.72 nM. Furthermore, the proposed method was also successfully applied for the detection of caspase-3 in cell lysate samples after apoptosis-inducing.